Current Trends and Potential Applications of Microbial Interactions for Human Welfare - Tshikantwa, Tiroyaone Shimane; Ullah, Muhammad Wajid; He, Feng; Yang, Guang (Frontiers in Microbiology, 2018)
For a long time, it was considered that interactions between microbes are only inhibitory in nature. However, latest developments in research have demonstrated that within our environment, several classes of microbes exist which produce different products upon interaction and thus embrace a wider scope of useful and potentially valuable aspects beyond simple antibiosis. Therefore, the current review explores different types of microbial interactions and describes the role of various physical, chemical, biological, and genetic factors regulating such interactions. It further explains the mechanism of action of biofilm formation and role of secondary metabolites regulating bacteria-fungi interaction. Special emphasis and focus is placed on microbial interactions which are important in medicine, food industry, agriculture, and environment. In short, this review reveals the recent contributions of microbial interaction for the benefit of mankind.